2015
DOI: 10.1186/s12885-015-1993-3
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ isoforms and receptors mRNA expression in breast tumours: prognostic value and clinical implications

Abstract: BackgroundTransforming growth factor beta (TGFβ) signalling is involved in both tumour suppression and tumour progression. The mRNA expression levels of the TGFβ isoforms and receptors in breast tumours may have prognostic value and clinical implications.MethodsThe mRNA levels of TGFB1, TGFB2, TGFB3, TGFBR1 and TGFBR2 were analysed in primary breast tumours and adjacent normal breast tissues, and the associations with tumour characteristics and patients’ overall and relapse-free survival were evaluated, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…These results have indicated that loss of TGFBR2 expression promotes epithelial oncogenesis. Several studies have shown that TGFBR2 inhibits cell growth, invasion, migration, and metastasis in breast and pancreatic cancer [30,31]. TCGA consortium and others have reported the mutations of TGFBR2 in ESCC [26].…”
Section: Discussionmentioning
confidence: 99%
“…These results have indicated that loss of TGFBR2 expression promotes epithelial oncogenesis. Several studies have shown that TGFBR2 inhibits cell growth, invasion, migration, and metastasis in breast and pancreatic cancer [30,31]. TCGA consortium and others have reported the mutations of TGFBR2 in ESCC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen markers were found to be differentially expressed: 7 lncRNAs, AC078802.1 to 2, BBC3-1, CHURC1-FNTB-1, FER3, RAD21-AS1-1, SLC39A8-1, and ZEB1-2 (Table 3A), none of which have current citations in PubMed; and, 10 mRNAs, upregulated: GLO1, GLTSCR2, TGFB1, RAB34; downregulated: IL2RA, INTS6, MXD1, RAB5B, TCF20 (SPBP), TLR2 (Table 3B); associations with breast or other cancers have previously been reported for all 10. [12][13][14][15][16][17][18][19][20][21] Of the upregulated mRNAs, TGFB1 and RAB34 are commonly cited as associated with proliferation and of the downregulated group INTS6 is cited as a tumor suppressor gene (search and review of the NCBI gene database https://www.ncbi. nlm.nih.gov/gene).…”
Section: Discussionmentioning
confidence: 99%
“…Since late metastasis has been confined to the reactivation of dormant DTCs, these results highlighted the coexistence of cell subpopulations at different points of the dormant-toawaken state. To resume proliferation, quiescent cells activate EGF, RAS, TGFb1, and TGFb3, which upregulation have been attributed to cause higher malignancy in breast tumors (Chen et al, 2015;Lo et al, 2006). To investigate the metastatic potential of NR2F1-AS1, we firstly tested whether NR2F1-AS1 influences anoikis resistance in BT474 cells.…”
Section: Nr2f1-as1 May Endow Metastatic Potential To Er-positive Breamentioning
confidence: 99%